(untitled) (Italian Journal of Public Health, 2007)
Background: Cardiovascular disease and malignancies account for more than 70% of all causes of mortality and morbidity in Italy. There is a subtle balance between genetic determinants and lifestyle, that often defines the line between health and sickness. So far studies aiming at identifying risk factors have mainly come from Northern Europe and the USA. It was to understand this balance between genetics and environmental determinants better, and to tailor appropriate preventive strategies for Italian and other Southern European populations, that theMoli-sani project was launched, transforming a small Italian region into a large scientific laboratory: the “Molise lab”. Methods: Each participant receives a thorough medical check-up at no cost to either him/her or the national health service, resulting in thousands of hours of free public health care. With a completely computerized system, Moli-sani is a “paperless” study, in which researchers and participants communicate using recently developed technologies such as mobile phone text messages (SMS). The newly established biological data bank (the “MoliBank”) will be one of the largest in Europe. Results: Early results of 8000 participants so far show a slightly worrying pattern of risk factors for a Mediterranean population. The prevalence of obesity, hypertension and metabolic syndrome is growing at rates close to those of other Western countries. Hypertension and, to a lesser extent, high blood glucose levels, are under-diagnosed and underestimated by patients, and appropriate therapy appears under-used and not very successful. However, cholesterol management appears more efficient. Conclusions: Paying particular attention towards innovation and new technologies, theMoli-sani project has placed itself at the cutting edge of a new paradigm crossing research and prevention.